CONGREGATION SATISFACTION TOWARDS SERVICES OF CHURCH MUSIC DEVELOPMENT COMMISSION AT GKJW JEMAAT SEMAMPIR - Akde Triyoga; Yoyok Febrijanto (Pedagogic Research-Applied Literacy Journal, 2025)
This study aims to describe the perception of Congregation towards the Service carried out by the Church Music Development Commission/ Komisi Pembinaan Musik Gereja (KPMG) in accompanying praise in worship. The research subjects were 60 congregations of GKJW Semampir using purposive sampling techniques. This study uses a quantitative method, research data were collected using a congregation satisfaction scale with 5 Service Quality Indicators according to Parasuraman as many as 13 items. The study was analyzed by frequency distribution, SPSS version 25.0 for windows. The results of the study showed that the Congregation's Satisfaction with the Church Music Development Commission Service was moderate. The Tangibles Indicator obtained was moderate, the Reliability Indicator obtained was moderate, the Responsiveness Indicator obtained was moderate, the Assurance Indicator obtained was high, and the Empathy Indicator obtained was high.